PhysicalPropertiesDistributionofGalaxyPopulationin Abell2142Cluster - KledsaiPoopakun (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
ThisworkaimstoinvestigatethephysicalpropertiesofsamplegalaxiesinAbell 2142cluster.Thephotometricandspectroscopicdatausinginthisworkwerecollected fromtheSloanDigitalSkySurvey(SDSS),selectedwithin2criteria;localedwithin100 arcminutesfromAbell2142centreandredshift0.0781≤z≤0.1038foravoideffectof backgroundandforeground.OurresultrevealsthatgalaxysampleinAbell2142canbe separatedinto2groupswhichgroupI(0.0781≤z≤0.0850),subclusterconnectingtothe filamentregion,andgroupII(0.0850 < z ≤0.1038),membersaroundtheclustercentral region.Moreover,Therelationbetweenapparentmagnitudein g filterbandandcolour indexsuggestthattheparameter u − z = 3.0canbeuseasacriteriatoseparatesamples intoblue(u − z ≤ 3.0)andred(u − z > 3.0)sequencegalaxies.Wealsoconsiderthe starformationactivityinthesample,wedefinedgalaxywiththeequivalentwidthofHα (EW(Hα) )greaterthan5Åasanactivegalaxyandfoundthatthesampleinsubcluster connectingtothefilamentregionshowsevidenceofstarformingactivitymorethanthe sampleinmembersaroundtheclustercentralregion.Thebluesequencegalaxiesalso tendtobemoreactivegalaxiesthanredsequencegalaxies.